Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

The essential oil composition of an Origanum majorana x O. vulgare ssp. vulgare backcross generation - J. Raskovic; B. Lukas; J. Novak (Biochemical Systematics and Ecology, 2026)

Thermomechanics coupling to Monte Carlo particle transport on unstructured mesh geometries using Cardinal - Mahmoud Eltawila; Pierre-Clément A. Simon; Guillaume L. Giudicelli; Helen Brooks; Nicholas Wozniak; April J. Novak (Annals of Nuclear Energy, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

It's not all about PFAS: Metal(loid)s are associated with physiological and metabolic changes in a native frog from conservation wetlands - Damian C. Lettoof; Rui Wang; Brad Clarke; Nicola Gray; Samuele Sala; Nick Bourne; William R. Richmond; Helen E. Nice; Peter Novak; Brenton von Takach; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

Dusky sharks actively prey on gray seals - Megan V. Winton; Ashleigh J. Novak; Victoria L. Migneco; John Chisholm; Gregory B. Skomal (Environmental Biology of Fishes, 2025)

P22-32 Knowledge Infrastructure supporting image-based characterisation of 2D graphene materials - P.P. Ankli; A.A. Abdelwahab; A. Logachov; R. Bugiel; D. Drobne; S. Novak; E. Kranjc; S. Saje; F. Pellegrino; E. Alladio; F. Sordello; E. Corrao; et al. (Toxicology Letters, 2025)

P09-54 Enhanced in vitroEvaluation of Sodium Iodide Symporter Inhibitors with Optional Biotransformation Pretreatment for Improved Physiological Relevance - K. Hilscherova; J. Novak; P. Kumari; S. Lungu-Mitea (Toxicology Letters, 2025)

ADMET parameters of tacrine and its metabolites confirm unsuitability of Sus scrofa f. domestica model to study tacrine-associated hepatotoxicity - M. Novak; J. Bureš; V. Radochová; J. Pejchal; L. Prchal; O. Soukup (Chemico-Biological Interactions, 2025)

Understanding Wave Attenuation Across Marshes: Insights from Numerical Modeling - Madeline R. Foster-Martinez; Ioannis Y. Georgiou; Duncan M. FitzGerald; Zoe J. Hughes; Alyssa Novak; Md Mohiuddin Sakib (Journal of Marine Science and Engineering, 2025)
Marsh vegetation dampens wave energy, providing protection to coastal communities from storms. A new modeling framework was applied to study wave height evolution over the saltmarsh bordering Newbury, MA. A regional Delft3D hydrodynamic model generated wind driver waves in the open water portions of the study area, which were then one-way coupled with an analytical model, the Marsh Transect Wave Attenuation (MTWA) model, which tracked wave evolution along select transects throughout the marsh. Field observations of vegetation and wave height evolution were used to calibrate MTWA. Seven scenarios were run covering a range of possible future management and environmental conditions, in addition to projected sea level rise. Results underscore the importance of vegetation and elevation to wave attenuation.

Early insights into the seasonal and spatial distribution of white sharks (Carcharodon carcharias) along the Maine coastline - Matthew M. Davis; Megan V. Winton; John A. Mohan; Joseph D. Iafrate; James A. Sulikowski; Blaise P. Jenner; Ashleigh J. Novak; Victoria Migneco; Tobey H. Curtis; Chip Michalove; Gregory B. Skomal (Frontiers in Marine Science, 2025)
While significant progress has been made to characterize life history patterns, movement ecology, and regional estimates of abundance of white sharks ( Carcharodon carcharias ) in the Western North Atlantic (WNA), patterns of spatial distribution remain relatively unknown in the northern Gulf of Maine. In this study, we utilize data collected from multiple acoustic telemetry projects from 2012-2023 to assess the spatiotemporal distribution of white sharks along sections of the Maine coastline and regional offshore waters. Acoustic receivers were deployed each year from 2012-2019 (mean number of receivers ± SD: 11 ± 4), and effort increased following the first-ever white shark related fatality in Maine in 2020 (2020-2023: 40 ± 15). In total, 107 white sharks tagged by researchers in the WNA were detected, with the majority (n = 90) detected in shallow (<50 m depth) waters post-2019. Reflective of the tagged population at-large, total length of individuals ranged from 2.1 to 4.9 m, with most individuals estimated to be in the juvenile or subadult life stages. White sharks were detected between the months of May-December, with peaks between July and September, and were observed in close proximity to several of Maine’s western beaches and islands/outcroppings, with higher numbers observed at several sites in eastern Casco Bay. Although the overall quantity of detections was relatively low when compared to white shark aggregation sites in other regions, this study provides baseline information on the presence of this species in the northern Gulf of Maine. While future research should include expanded receiver coverage in eastern Maine and the use of additional tagging technologies, this study contributes early insights for informing marine spatial planning, fisheries management, and conservation strategies for white sharks in the region.

Optimisation of high-rate filamentous algal pond operating parameters for nutrient bioremediation of primary municipal wastewater - Indira N. Novak; Marie Magnusson; Rupert J. Craggs; Rebecca J. Lawton (Algal Research, 2025)

Determinants of antimicrobial resistance in biosolids: A systematic review, database, and meta-analysis - Joanna Ciol Harrison; Grace V. Morgan; Aditya Kuppravalli; Nicole Novak; Michael Farrell; Sienna Bircher; Emily Garner; Nicholas J. Ashbolt; Amy Pruden; Rebecca L. Muenich; Treavor H. Boyer; Clinton Williams; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Screening protocol for freshwater filamentous macroalgae bioremediation of primary municipal wastewater - Indira N. Novak; Marie Magnusson; Rupert J. Craggs; Rebecca J. Lawton (Journal of Applied Phycology, 2024)
A screening protocol was developed and applied to isolate and select cultivars of freshwater filamentous macroalgae for year-round monoculture cultivation and nutrient bioremediation of primary municipal wastewater. The screening protocol is a step-by-step guide to identify robust cultivars which possess key attributes of competitive dominance, high biomass productivity and bioremediation performance under local seasonal and extreme conditions. Forty-four mixed samples of freshwater filamentous macroalgae were collected during summer and winter from a range of local aquatic environments. Eleven isolated cultivars were grown in primary treated municipal wastewater and their biomass productivity and bioremediation performance under local ambient (summer and winter), extreme summer (max. summer) and winter (min. winter) conditions were assessed. Extreme conditions proved to be an important determining factor for cultivar selection as biomass productivity and bioremediation performance significantly declined under min. winter conditions. However, biomass productivity was not directly related to bioremediation performance, as cultivars with low growth rates maintained high nutrient removal rates under min. winter conditions. Top performing cultivars were Klebsormidium sp. (KLEB B) which reduced total ammoniacal-N concentrations by 99.9% to 0.01 mg L -1 (± 0.01 SE), Oedogonium sp. (OEDO D) which reduced nitrate-N concentrations by 90.2% to 0.08 mg L -1 (± 0.7 SE) and Rhizoclonium sp. which reduced phosphate concentrations by 98.7% to 0.02 mg L -1 (± 0.01 SE). Based on overall biomass productivity and bioremediation performance across seasonal and extreme conditions Klebsormidium sp. (KLEB B) , Stigeoclonium sp. (STIG A) and Ulothrix sp. were identified as top performing cultivars suitable for the nutrient bioremediation of primary municipal wastewater.

P19-45 Data management for image-based characterisation of 2D nano-materials - P.P. Ankli; A. Ali; S. Hodzic; A. Logachov; K. Maciejczuk; A. Milochiv; S. Hardy; B. Hardy; S. Novak; E. Kranjc; V. Kononenko; S. Saje; et al. (Toxicology Letters, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Mixing behavior of dissolved organic matter at the Yukon and Kolyma land ocean interface - Anne M. Kellerman; Peter J. Hernes; Amy M. McKenna; J. Blake Clark; Augusta Edmund; Brice Grunert; Paul J. Mann; Antonio Mannino; Michael Novak; Aron Stubbins; Maria Tzortziou; Nikita Zimov; et al. (Marine Chemistry, 2023)

Scavenger receptor BI attenuates oxidized phospholipid-induced pulmonary inflammation - Katelyn Dunigan-Russell; Michael J. Yaeger; Myles X. Hodge; Brita Kilburg-Basnyat; Sky W. Reece; Anastasiya Birukova; Marissa A. Guttenberg; Caymen Novak; Sangwoon Chung; Brandie Michelle Ehrmann; E. Diane Wallace; Debra Tokarz; et al. (Toxicology and Applied Pharmacology, 2023)

Environmental and bioclimatic factors influencing yeasts and molds distribution along European shores - M. Cogliati; S. Arikan-Akdagli; A. Barac; A.C. Bostanaru; S. Brito; N. Çerikçioğlu; M.A. Efstratiou; Ç. Ergin; M.C. Esposto; M. Frenkel; J.P. Gangneux; A. Gitto; et al. (Science of The Total Environment, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Arctic biogeochemical and optical properties of dissolved organic matter across river to sea gradients - Michael G. Novak; Antonio Mannino; J. Blake Clark; Peter Hernes; Maria Tzortziou; Robert G. M. Spencer; Anne M. Kellerman; Brice Grunert (Frontiers in Marine Science, 2022)
Arctic landscapes are warming and becoming wetter due to changes in precipitation and the timing of snowmelt which consequently alters seasonal runoff and river discharge patterns. These changes in hydrology lead to increased mobilization and transport of terrestrial dissolved organic matter (DOM) to Arctic coastal seas where significant impacts on biogeochemical cycling can occur. Here, we present measurements of dissolved organic carbon (DOC) and chromophoric DOM (CDOM) in the Yukon River-to-Bering Sea system and two river plumes on the Alaska North Slope which flow into the Beaufort Sea. Our sampling characterized optical and biogeochemical properties of DOM during high and low river discharge periods for the Yukon River-Bering Sea system. The average DOC concentration at the multiple Yukon River mouths ranged from a high of 10.36 mg C L -1 during the ascending limb of the 2019 freshet (late May), 6.4 mg C L -1 during the descending limb of the 2019 freshet (late June), and a low of 3.86 mg C L -1 during low river discharge in August 2018. CDOM absorption coefficient at 412 nm ( a CDOM (412)) averaged 8.23 m -1 , 5.07 m -1 , and 1.9 m -1 , respectively. Several approaches to model DOC concentration based on its relationship with CDOM properties demonstrated cross-system seasonal and spatial robustness for these Arctic coastal systems despite spanning an order of magnitude decrease in DOC concentration from the lower Yukon River to the Northern Bering Sea as well as the North Slope systems. “Snapshot” fluxes of DOC and CDOM across the Yukon River Delta to Norton Sound were calculated from our measurements and modeled water fluxes forced with upstream USGS river gauge data. Our findings suggest that during high river flow, DOM reaches the delta largely unaltered by inputs or physical and biogeochemical processing and that the transformations of Yukon River DOM largely occur in the plume. However, during low summer discharge, multiple processes including local precipitation events, microbial decomposition, photochemistry, and likely others can alter the DOM properties within the lower Yukon River and Delta prior to flowing into Norton Sound.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Following the Sand Grains - Duncan M. FitzGerald; Zoe J. Hughes; Alice Staro; Christopher J. Hein; Md Mohiuddin Sakib; Ioannis Y. Georgiou; Alyssa Novak (Journal of Marine Science and Engineering, 2022)
When longshore transport systems encounter tidal inlets, complex mechanisms are involved in bypassing sand to downdrift barriers. Here, this process is examined at Plum Island Sound and Essex Inlets, Massachusetts, USA. One major finding from this study is that sand is transferred along the coast—especially at tidal inlets—by parcels, in discrete steps, and over decadal-scale periods. The southerly orientation of the main-ebb channel at Plum Island Sound, coupled with the landward migration of bars from the ebb delta to the central portion of the downdrift Castle Neck barrier island, have formed a beach protuberance. During the constructional phase, sand is sequestered at the protuberance and the spit-end of the barrier becomes sediment starved, leading to shoreline retreat and a broadening of the spit platform at the mouth to Essex Bay (downdrift side of Castle Neck). Storm-induced sand transport from erosion of the spit and across the spit platform is washed into Essex Bay, filling channels and enlarging flood deltas. This study illustrates the pathways and processes of sand transfer along the shoreline of a barrier-island/tidal-inlet system and provides an important example of the processes that future hydrodynamic and sediment-transport modeling should strive to replicate.

Coral adaptation to climate change: Meta‐analysis reveals high heritability across multiple traits - Kevin R. Bairos‐Novak; Mia O. Hoogenboom; Madeleine J. H. van Oppen; Sean R. Connolly (Global Change Biology, 2021)
Anthropogenic climate change is a rapidly intensifying selection pressure on biodiversity across the globe and, particularly, on the world's coral reefs. The rate of adaptation to climate change is proportional to the amount of phenotypic variation that can be inherited by subsequent generations (i.e., narrow‐sense heritability, h 2 ). Thus, traits that have higher heritability (e.g., h 2 > 0.5) are likely to adapt to future conditions faster than traits with lower heritability (e.g., h 2 h 2 h 2 = 0.25–0.50) of photochemistry, growth, and bleaching, and high heritability ( h 2 > 0.50) for metrics related to survival and immune responses. Some of these values are higher than typically observed in other taxa, such as survival and growth, while others were more comparable, such as gene expression and photochemistry. There was no detectable effect of temperature on heritability, but narrow‐sense heritability estimates were generally lower than broad‐sense estimates, indicative of significant non‐additive genetic variation across traits. Trait heritability also varied depending on coral life stage, with bleaching and growth in juveniles generally having lower heritability compared to bleaching and growth in larvae and adults. These differences may be the result of previous stabilizing selection on juveniles or may be due to constrained evolution resulting from genetic trade‐offs or genetic correlations between growth and thermotolerance. While we find no evidence that heritability decreases under temperature stress, explicit tests of the heritability of thermal tolerance itself—such as coral thermal reaction norm shape—are lacking. Nevertheless, our findings overall reveal high trait heritability for the majority of coral traits, suggesting corals may have a greater potential to adapt to climate change than has been assumed in recent evolutionary models.

A Novel Framework to Predict Relative Habitat Selection in Aquatic Systems: Applying Machine Learning and Resource Selection Functions to Acoustic Telemetry Data From Multiple Shark Species - Lucas P. Griffin; Grace A. Casselberry; Kristen M. Hart; Adrian Jordaan; Sarah L. Becker; Ashleigh J. Novak; Bryan M. DeAngelis; Clayton G. Pollock; Ian Lundgren; Zandy Hillis-Starr; Andy J. Danylchuk; Gregory B. Skomal (Frontiers in Marine Science, 2021)
Resource selection functions (RSFs) have been widely applied to animal tracking data to examine relative habitat selection and to help guide management and conservation strategies. While readily used in terrestrial ecology, RSFs have yet to be extensively used within marine systems. As acoustic telemetry continues to be a pervasive approach within marine environments, incorporation of RSFs can provide new insights to help prioritize habitat protection and restoration to meet conservation goals. To overcome statistical hurdles and achieve high prediction accuracy, machine learning algorithms could be paired with RSFs to predict relative habitat selection for a species within and even outside the monitoring range of acoustic receiver arrays, making this a valuable tool for marine ecologists and resource managers. Here, we apply RSFs using machine learning to an acoustic telemetry dataset of four shark species to explore and predict species-specific habitat selection within a marine protected area. In addition, we also apply this RSF-machine learning approach to investigate predator-prey relationships by comparing and averaging tiger shark relative selection values with the relative selection values derived for eight potential prey-species. We provide methodological considerations along with a framework and flexible approach to apply RSFs with machine learning algorithms to acoustic telemetry data and suggest marine ecologists and resource managers consider adopting such tools to help guide both conservation and management strategies.

Correction to: Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)

Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)
Increasing the protection of coastal vegetated ecosystems has been suggested as one strategy to compensate for increasing carbon dioxide (CO 2 ) in the atmosphere as the capacity of these habitats to sequester and store carbon exceeds that of terrestrial habitats. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems and have an exceptional ability to sequester and store large quantities of carbon in biomass and, particularly, in sediments. However, carbon stocks (C org stocks) and carbon accumulation rates (C org accumulation) in seagrass meadows are highly variable both spatially and temporally, making it difficult to extrapolate this strategy to areas where information is lacking. In this study, C org stocks and C org accumulation were determined at 11 eelgrass meadows across New England, representing a range of eutrophication and exposure conditions. In addition, the environmental factors and structural characteristics of meadows related to variation in C org stocks were identified. The objectives were accomplished by assessing stable isotopes of δ 13 C and δ 15 N as well as %C and %N in plant tissues and sediments, measuring grain size and 210 Pb of sediment cores, and through assessing site exposure. Variability in C org stocks in seagrass meadows is well predicted using commonly measured environmental variables such as grain size distribution. This study allows incorporation of data and insights for the northwest Atlantic, where few studies on carbon sequestration by seagrasses have been conducted.

Genetic analysis of invasive populations of Ventenata dubia (Poaceae): an assessment of propagule pressure and pattern of range expansion in the Western United States - Inna Pervukhina-Smith; René F. H. Sforza; Massimo Cristofaro; James F. Smith; Stephen J. Novak (Biological Invasions, 2020)

Estimation of the Effect of OAT2-Mediated Active Uptake on Meloxicam Exposure in the Human Liver - Rui Li; Sumathy Mathialagan; Jonathan J. Novak; Heather Eng; Keith Riccardi; John Litchfield (The AAPS Journal, 2020)

Coarse- and fine-scale acoustic telemetry elucidates movement patterns and temporal variability in individual territories for a key coastal mesopredator - Sarah L. Becker; John T. Finn; Ashleigh J. Novak; Andy J. Danylchuk; Clayton G. Pollock; Zandy Hillis-Starr; Ian Lundgren; Adrian Jordaan (Environmental Biology of Fishes, 2020)

Planning for Change: Assessing the Potential Role of Marine Protected Areas and Fisheries Management Approaches for Resilience Management in a Changing Ocean - Kristy Kroeker; Mark Carr; Peter Raimondi; Jennifer Caselle; Libe Washburn; Stephen Palumbi; John Barth; Francis Chan; Bruce Menge; Kristen Milligan; Mark Novak; J. Wilson White (Oceanography, 2019)

Community Responses to Climate-Related Variability and Disease: The Critical Importance of Long-Term Research - Bruce Menge; Jennifer Caselle; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Sarah Gravem; Tarik Gouhier; Jane Lubchenco; Margaret McManus; Kristen Milligan; Mark Novak; et al. (Oceanography, 2019)

Integrating Coastal Oceanic and Benthic Ecological Approaches for Understanding Large-Scale Meta-Ecosystem Dynamics - Bruce Menge; Jennifer Caselle; Kristen Milligan; Sarah Gravem; Tarik Gouhier; J. Wilson White; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Jane Lubchenco; Margaret McManus; et al. (Oceanography, 2019)

PISCO: Advances Made Through the Formation of a Large-Scale, Long-Term Consortium for Integrated Understanding of Coastal Ecosystem Dynamics - Bruce Menge; Kristen Milligan; Jennifer Caselle; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Robert Cowen; Mark Denny; Steven Gaines; Gretchen Hofmann; Kristy Kroeker; et al. (Oceanography, 2019)

How is agroforestry perceived in Europe? An assessment of positive and negative aspects by stakeholders - Silvestre García de Jalón; Paul J. Burgess; Anil Graves; Gerardo Moreno; Jim McAdam; Eric Pottier; Sandra Novak; Valerio Bondesan; Rosa Mosquera-Losada; Josep Crous-Durán; Joao H. N. Palma; Joana A. Paulo; et al. (Agroforestry Systems, 2018)

What drives interaction strengths in complex food webs? A test with feeding rates of a generalist stream predator - Daniel L. Preston; Jeremy S. Henderson; Landon P. Falke; Leah M. Segui; Tamara J. Layden; Mark Novak (Ecology, 2018)
Describing the mechanisms that drive variation in species interaction strengths is central to understanding, predicting, and managing community dynamics. Multiple factors have been linked to trophic interaction strength variation, including species densities, species traits, and abiotic factors. Yet most empirical tests of the relative roles of multiple mechanisms that drive variation have been limited to simplified experiments that may diverge from the dynamics of natural food webs. Here, we used a field‐based observational approach to quantify the roles of prey density, predator density, predator‐prey body‐mass ratios, prey identity, and abiotic factors in driving variation in feeding rates of reticulate sculpin ( Cottus perplexus ). We combined data on over 6,000 predator‐prey observations with prey identification time functions to estimate 289 prey‐specific feeding rates at nine stream sites in Oregon. Feeding rates on 57 prey types showed an approximately log‐normal distribution, with few strong and many weak interactions. Model selection indicated that prey density, followed by prey identity, were the two most important predictors of prey‐specific sculpin feeding rates. Feeding rates showed a positive relationship with prey taxon densities that was inconsistent with predator saturation predicted by current functional response models. Feeding rates also exhibited four orders‐of‐magnitude in variation across prey taxonomic orders, with the lowest feeding rates observed on prey with significant anti‐predator defenses. Body‐mass ratios were the third most important predictor variable, showing a hump‐shaped relationship with the highest feeding rates at intermediate ratios. Sculpin density was negatively correlated with feeding rates, consistent with the presence of intraspecific predator interference. Our results highlight how multiple co‐occurring drivers shape trophic interactions in nature and underscore ways in which simplified experiments or reliance on scaling laws alone may lead to biased inferences about the structure and dynamics of species‐rich food webs.

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Efficacy of remote underwater video cameras for monitoring tropical wetland fishes - Alison J. King; Amy George; Duncan J. Buckle; Peter A. Novak; Christopher J. Fulton (Hydrobiologia, 2018)

Advantage of multispectral imaging with sub-centimeter resolution in precision agriculture: generalization of training for supervised classification - F. Rodriguez-Moreno; J. Kren; F. Zemek; J. Novak; V. Lukas; M. Pikl (Precision Agriculture, 2017)

Consequences of inoculation with native arbuscular mycorrhizal fungi for root colonization and survival of Artemisia tridentata ssp. wyomingensis seedlings after transplanting - Bill E. Davidson; Stephen J. Novak; Marcelo D. Serpe (Mycorrhiza, 2016)

Soil Health, Crop Productivity, Microbial Transport, and Mine Spoil Response to Biochars - J. M. Novak; J. A. Ippolito; R. D. Lentz; K. A. Spokas; C. H. Bolster; K. Sistani; K. M. Trippe; C. L. Phillips; M. G. Johnson (BioEnergy Research, 2016)

17β-Estradiol influent and effluent concentrations in wastewater: demographic influences and the risk to environmental health - K. T. Heffron; K. F. Gaines; J. M. Novak; T. Canam; D. A. Collard (Environmental Monitoring and Assessment, 2016)

ATP release, generation and hydrolysis in exocrine pancreatic duct cells - J. M. Kowal; G. G. Yegutkin; I. Novak (Purinergic Signalling, 2015)

Plant Macro- and Micronutrient Dynamics in a Biochar-Amended Wetland Muck - J. M. Novak; G. C. Sigua; K. A. Spokas; W. J. Busscher; K. B. Cantrell; D. W. Watts; B. Glaz; P. G. Hunt (Water, Air, & Soil Pollution, 2015)

Progressive migration and anagenesis in Drimys confertifolia of the Juan Fernández Archipelago, Chile - Patricio López-Sepúlveda; Koji Takayama; Josef Greimler; Daniel J. Crawford; Patricio Peñailillo; Marcelo Baeza; Eduardo Ruiz; Gudrun Kohl; Karin Tremetsberger; Alejandro Gatica; Luis Letelier; Patricio Novoa; et al. (Journal of Plant Research, 2015)

Erratum to: Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Role of vesicular nucleotide transporter VNUT (SLC17A9) in release of ATP from AR42J cells and mouse pancreatic acinar cells - K. A. Haanes; J. M. Kowal; G. Arpino; S. C. Lange; Y. Moriyama; P. A. Pedersen; I. Novak (Purinergic Signalling, 2014)

Phenolic Acid Sorption to Biochars from Mixtures of Feedstock Materials - K. E. Hall; M. J. Calderon; K. A. Spokas; L. Cox; W. C. Koskinen; J. Novak; K. Cantrell (Water, Air, & Soil Pollution, 2014)

Distribution of Structural Carbohydrates in Corn Plants Across the Southeastern USA - Spyridon Mourtzinis; Keri B. Cantrell; Francisco J. Arriaga; Kipling S. Balkcom; Jeff M. Novak; James R. Frederick; Douglas L. Karlen (BioEnergy Research, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Designing relevant biochars as soil amendments using lignocellulosic-based and manure-based feedstocks - Jeffrey M. Novak; Keri B. Cantrell; Donald W. Watts; Warren J. Busscher; Mark G. Johnson (Journal of Soils and Sediments, 2014)

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Polar bear stress hormone cortisol fluctuates with the North Atlantic Oscillation climate index - Thea Ø. Bechshøft; Christian Sonne; Frank F. Rigét; Robert J. Letcher; Melinda A. Novak; Elizabeth Henchey; Jerrold S. Meyer; Igor Eulaers; Veerle L. B. Jaspers; Adrian Covaci; Rune Dietz (Polar Biology, 2013)

Compositional and Thermal Evaluation of Lignocellulosic and Poultry Litter Chars via High and Low Temperature Pyrolysis - J. M. Novak; K. B. Cantrell; D. W. Watts (BioEnergy Research, 2013)

Effects of aging on apoptosis gene expression in oral mucosal tissues - Octavio A. Gonzalez; M. John Novak; Sreenatha Kirakodu; Arnold J. Stromberg; Shu Shen; Luis Orraca; Janis Gonzalez-Martinez; Jeffrey L. Ebersole (Apoptosis, 2013)

Essential oil composition and antioxidant activity of Stachys sylvatica L. (Lamiaceae) from different wild populations in Kosovo - A. Hajdari; J. Novak; B. Mustafa; C. Franz (Natural Product Research, 2012)

Role of FAT/CD36 in novel PKC isoform activation in heart of spontaneously hypertensive rats - Martina J. Klevstig; Irena Markova; Jana Burianova; Ludmila Kazdova; Michal Pravenec; Olga Novakova; Frantisek Novak (Molecular and Cellular Biochemistry, 2011)

Cytokinin Primes Plant Responses to Wounding and Reduces Insect Performance - Christopher Dervinis; Christopher J. Frost; Susan D. Lawrence; Nicole G. Novak; John M. Davis (Journal of Plant Growth Regulation, 2010)

Phenotypic divergence during the invasion of Phyla canescens in Australia and France: evidence for selection‐driven evolution - Cheng‐Yuan Xu; Mic H. Julien; Mohammad Fatemi; Christophe Girod; Rieks D. Van Klinken; Caroline L. Gross; Stephen J. Novak (Ecology Letters, 2010)
Rapid adaptive evolution has been advocated as a mechanism that promotes invasion. Demonstrating adaptive evolution in invasive species requires rigorous analysis of phenotypic shifts driven by selection. Here, we document selection‐driven evolution of Phyla canescens , an Argentine weed, in two invaded regions (Australia and France). Invasive populations possessed similar or higher diversity than native populations, and displayed mixed lineages from different sources, suggesting that genetic bottlenecks in both countries might have been alleviated by multiple introductions. Compared to native populations, Australian populations displayed more investment in sexual reproduction, whereas French populations possessed enhanced vegetative reproduction and growth. We partitioned evolutionary forces (selection vs. stochastic events) using two independent methods. Results of both analyses suggest that the pattern of molecular and phenotypic variability among regions was consistent with selection‐driven evolution, rather than stochastic events. Our findings indicate that selection has shaped the evolution of P . canescens in two different invaded regions. Ecology Letters (2010) 13: 32–44

Benefits of Supplementation of an Electrolyte Scour Treatment with a Bacillus-Based Direct-Fed Microbial for Calves - C. A. Wehnes; K. N. Novak; V. Patskevich; D. R. Shields; J. A. Coalson; A. H. Smith; M. E. Davis; T. G. Rehberger (Probiotics and Antimicrobial Proteins, 2009)

Geospatial variability in the egg raft distribution and abundance of Culex pipiens and Culex restuans in Urbana‐Champaign, Illinois - B. G. Jacob; R. L. Lampman; M. P. Ward; E. J. Muturi; J. A. Morris; E. X. Caamano; R. J. Novak (International Journal of Remote Sensing, 2009)

Clapper rails as indicators of mercury and PCB bioavailability in a Georgia saltmarsh system - J. C. Cumbee; K. F. Gaines; G. L. Mills; N. Garvin; W. L. Stephens; J. M. Novak; I. L. Brisbin (Ecotoxicology, 2008)

Potato, Solanum Tuberosum, Defense Against Colorado Potato Beetle, Leptinotarsa Decemlineata (Say): Microarray Gene Expression Profiling of Potato by Colorado Potato Beetle Regurgitant Treatment of Wounded Leaves - Susan D. Lawrence; Nicole G. Novak; Chelsea J.-T. Ju; Janice E. K. Cooke (Journal of Chemical Ecology, 2008)

How do larvae attach to a solid in a laminar flow? - G. Zilman; J. Novak; Y. Benayahu (Marine Biology, 2008)

Three-dimensional simulations and wind-tunnel experiments on airflow over isolated forest stands - Terry L. Clark; Stephen J. Mitchell; Michael Novak (Boundary-Layer Meteorology, 2007)

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

Arbuscular mycorrhiza alter the concentration of essential oils in oregano (Origanum sp., Lamiaceae) - T. Khaosaad; H. Vierheilig; M. Nell; K. Zitterl-Eglseer; J. Novak (Mycorrhiza, 2006)

The effect of varying levels of sodium bicarbonate on polychlorinated biphenyl dechlorination in Hudson River sediment cultures - Tao Yan; Timothy M. LaPara; Paige J. Novak (Environmental Microbiology, 2006)
Summary The addition of different concentrations of sodium bicarbonate had a profound effect on 2,3,4,5‐chlorobiphenyl (2,3,4,5‐CB) dechlorination in Hudson River sediment cultures. The most extensive dechlorination was observed in cultures to which 100 mg l −1 bicarbonate was added. Cultures amended with 1000 mg l −1 bicarbonate had the least extensive dechlorination, with 2,4‐CB and 2,5‐CB as predominant end‐products. A significant loss of total chlorinated biphenyl mass was observed in cultures to which ≤ 500 mg l −1 bicarbonate was added, suggesting that degradation beyond chlorinated biphenyls occurred. The dynamics of acetate formation were different among the treatments, with high acetate concentrations detected throughout the 303‐day experiment in cultures to which 1000 mg l −1 bicarbonate had been added. Sodium bicarbonate addition also had a significant impact on bacterial community structure as detected by polymerase chain reaction‐denaturant gradient gel electrophoresis (PCR‐DGGE) of 16S rRNA gene fragments. Three putative polychlorinated biphenyl (PCB) dechlorinators were identified; one Dehalococcoides ‐like population was detected in all enrichment cultures, whereas two Dehalobacter ‐like populations were only detected in the enrichment cultures with the most extensive dechlorination. These results suggest that the availability of bicarbonate, and potentially sodium, may affect PCB dechlorination in Hudson River sediment and thus need to be taken into consideration when assessing the fate of PCBs or implementing bioremediation.

Element Levels in Snakes in South Carolina: Differences Between a Control Site and Exposed Site on the Savannah River Site - J. Burger; S. Murray; K. F. Gaines; J. M. Novak; T. Punshon; C. Dixon; M. Gochfeld (Environmental Monitoring and Assessment, 2006)

Respiratory and Reproductive Characteristics of Eastern Mosquitofish (Gambusia holbrooki) Inhabiting a Coal Ash Settling Basin - B. P. Staub; W. A. Hopkins; J. Novak; J. D. Congdon (Archives of Environmental Contamination and Toxicology, 2004)

Features of motor performance that drive adaptation in rapid hand movements - K. Novak; L. Miller; J. Houk (Experimental Brain Research, 2003)

The use of overlapping submovements in the control of rapid hand movements - K. E. Novak; L. E. Miller; J. C. Houk (Experimental Brain Research, 2002)

Regulation of the Na+/Ca2+ Exchanger in Rat Pancreatic Ducts - I. Ankorina-Stark; J. Amstrup; I. Novak (The Journal of Membrane Biology, 2002)

Submaximal exercise in healthy volunteers: the relationship between gastric mucosal and systemic energy status - R. Rokyta; M. Matejovic; I. Novak; V. Zeman; A. Krouzecky; J. Novak; L. Trefil; K. Linhartova; V. Sramek (Pflügers Archiv - European Journal of Physiology, 2002)

Influence of Soil Aggregate Size on Atrazine and Trifluralin Leaching - S. M. Novak; J.-M. Portal; M. Schiavon (Bulletin of Environmental Contamination and Toxicology, 2001)

Development of a hybrid variety system in marjoram (Origanum majorana L.) - J. Langbehn; F. Pank; J. Novak; W.D. Blüthner; Ch. Franz; W. Junghanns; C. Vender (Euphytica, 2001)

Positioning of five genes (CASK, ARX, SAT, IMAGE cDNAs 248928 and 253949) from the human X Chromosome short arm with respect to evolutionary breakpoints on the mouse X Chromosome - Helen J. Blair; Vivienne Reed; Emmanuelle Gormally; Joanna B. Wilson; Jakub Novak; Roderick R. McInnes; Sandra J. Phillips; Benjamin A. Taylor; Yvonne Boyd (Mammalian Genome, 2000)

Mosquitocidal Activity of Acetylenic Compounds from Cryptotaenia canadensis - U. Eckenbach; R. L. Lampman; D. S. Seigler; J. Ebinger; R. J. Novak (Journal of Chemical Ecology, 1999)

Iron precipitation kinetics in synthetic acid mine drainage - Harry R. Diz; John T. Novak; J. Donald Rimstidt (Mine Water and the Environment, 1999)

Effects of climatic variability on the annual carbon sequestration by a boreal aspen forest - W. J. Chen; T. A. Black; P. C. Yang; A. G. Barr; H. H. Neumann; Z. Nesic; P. D. Blanken; M. D. Novak; J. Eley; R. J. Ketler; R. Cuenca (Global Change Biology, 1999)
To evaluate the carbon budget of a boreal deciduous forest, we measured CO 2 fluxes using the eddy covariance technique above an old aspen (OA) forest in Prince Albert National Park, Saskatchewan, Canada, in 1994 and 1996 as part of the Boreal Ecosystem‐Atmosphere Study (BOREAS). We found that the OA forest is a strong carbon sink sequestering 200 ± 30 and 130 ± 30 g C m –2 y –1 in 1994 and 1996, respectively. These measurements were 16–45% lower than an inventory result that the mean carbon increment was about 240 g C m –2 y –1 between 1919 and 1994, mainly due to the advanced age of the stand at the time of eddy covariance measurements. Assuming these rates to be representative of Canadian boreal deciduous forests (area ≈ 3 × 10 5 km 2 ), it is likely they can sequester 40–60 Tg C y –1 , which is 2–3% of the missing global carbon sink. The difference in carbon sequestration by the OA forest between 1994 and 1996 was mainly caused by the difference in leaf emergence date. The monthly mean air temperature during March–May 1994, was 4.8 °C higher than in 1996, resulting in leaf emergence being 18–24 days earlier in 1994 than 1996. The warm spring and early leaf emergence in 1994 enabled the aspen forest to exploit the long days and high solar irradiance of mid‐to‐late spring. In contrast, the 1996 OA growing season included only 32 days before the summer solstice. The earlier leaf emergence in 1994 resulted 16% more absorbed photosynthetically active radiation and a 90 g C m –2 y –1 increase in photosynthesis than 1996. The concomitant increase in respiration in the warmer year (1994) was only 20 g C m –2 y –1 . These results show that an important control on carbon sequestration by boreal deciduous forests is spring temperature, via the influence of air temperature on the timing of leaf emergence.

Different purinergic receptors lead to intracellular calcium increases in pancreatic ducts - B. C. Christoffersen; M. J. Hug; I. Novak (Pflügers Archiv - European Journal of Physiology, 1998)

Protein kinase C and calcium/calmodulin-dependent protein kinase II phosphorylate three-repeat and four-repeat tau isoforms at different rates - Toolsee J. Singh; Inge Grundke-Iqbal; Wu Qiongli Wu; Ved Chauhan; Michal Novak; Eva Kontzekova; Khalid Iqbal (Molecular and Cellular Biochemistry, 1997)

Replication of human cytomegalovirus in a rhabdomyosarcoma cell line depends on the state of differentiation of the cells - J. Cinatl; J. Cinatl; K. Radsak; H. Rabenau; B. Weber; M. Novak; R. Benda; B. Kornhuber; H. W. Doerr (Archives of Virology, 1994)

Long-term monitoring of polychlorinated biphenyls in the Hudson River (New York) using caddisfly larvae and other macroinvertebrates - M. A. Novak; A. A. Reilly; S. J. Jackling (Archives of Environmental Contamination and Toxicology, 1988)